2011
DOI: 10.1111/j.1467-9515.2011.00794.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Social Welfare Programmes in East Asia: A Case Study of Taiwan

Abstract: Using the 2008 Family Income and Expenditure Survey, this study examined the effectiveness of social welfare programmes in Taiwan. The empirical evidence shows that most types of social welfare spending were limited in 2008. However, the social welfare programmes that were in place substantially reduced income inequality in Taiwan. Using the Organisation for Economic Co-operation and Development (OECD) poverty threshold, the results reveal that 14 per cent of the sample's families were poor in terms of market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In Taiwan, almost total enrollment of adolescents in higher education generates a 'ceiling effect' of keen competition in educational attainment and labor market entry, and families' cultural and social capital resources also serve as a precondition for the maintenance of intergenerational status. Moreover, being an island of limited size favors a relatively homogeneous social structure and production regime (Kim 2016;Huang and Ku 2011;Feng and Han 2010). China's welfare regime leans more toward the United States, whereas Taiwan's shows similarities with Germany in terms of redistribution and social inclusion.…”
Section: Societal Differences Between the United States Germany Taimentioning
confidence: 99%
“…In Taiwan, almost total enrollment of adolescents in higher education generates a 'ceiling effect' of keen competition in educational attainment and labor market entry, and families' cultural and social capital resources also serve as a precondition for the maintenance of intergenerational status. Moreover, being an island of limited size favors a relatively homogeneous social structure and production regime (Kim 2016;Huang and Ku 2011;Feng and Han 2010). China's welfare regime leans more toward the United States, whereas Taiwan's shows similarities with Germany in terms of redistribution and social inclusion.…”
Section: Societal Differences Between the United States Germany Taimentioning
confidence: 99%
“…Using the 2008 Family Income and Expenditure Survey, Huang and Ku (2011) found that family structure in Taiwan is quite diverse, and the percentages of the various types of family structures were notably different from the Downloaded by [University of Liverpool] at 08:23 05 January 2015 percentages in the United States and Europe. First, extended families made up one third of two-parent families with children, whereas nuclear families composed two thirds of two-parent families with children.…”
Section: Previous Research On Resource Allocationmentioning
confidence: 96%
“…9% in 20079% in (DGBAS, 2008. In other words, despite Taiwan's political democratization, social welfare programs increased relatively little and thus had only modest effects on reducing poverty for families in need (Huang & Ku, 2011;Ku, 2003).…”
Section: The Development Of Social Welfare Programs In Taiwanmentioning
confidence: 97%
See 2 more Smart Citations